Primary vitreoretinal lymphoma: diagnosis, treatment, and prognosis—a review of current knowledge and future directions - Si-Yu Wang; Suo-Wang Zhou; Jing Gao; Liang Wang (Blood Science)
Primary vitreoretinal lymphoma (PVRL), a rare subtype of primary central nervous system lymphoma (PCNSL), can lead to permanent vision loss and central nervous system (CNS) involvement, resulting in a poor prognosis. PVRL often masquerades as uveitis, and its partial response to topical corticosteroids further complicates the diagnosis. The gold standard for diagnosis is cytological analysis; however, owing to its low sensitivity, cytokine profiling and genetic testing may serve as supplementary diagnostic tools. There is no universally accepted consensus regarding PVRL treatment protocols. Combined systemic high-dose intravenous methotrexate (MTX) and intravitreal therapy may help manage bilateral ocular lesions, although this combination’s ability to delay CNS relapse remains controversial. For relapsed or refractory (R/R) PVRL patients aged <60 years, intensive consolidation chemotherapy followed by autologous stem cell transplantation may be considered. Novel targeted therapies such as ibrutinib and lenalidomide have demonstrated efficacy in R/R cases. Large-scale multicenter prospective studies are urgently needed to determine optimal treatment strategies.